PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 1 YEHKUNING - PRIANTINI, DEWA AYU MADE MANU OKTA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2018)
ABSTRACTÂ Â Â Â Â Â Â Education is one of manifestation of dynamic human culture and sarad of culture. Therefore, the development or change in education is something that must happen in line with the changing culture of life. The purpose of this education will be achieved well if the chosen teaching method or model can be applied seriously and the students more easily understand the lesson material presented, the students are more passionate, and happy to learn. Among the various methods and models available, researchers chose the